Transient incubation of cultured hippocampal neurons in the absence of magnesium induces rhythmic and synchronized epileptiform-like activity - Mele, Miranda (2021)
Cell culture models are important tools to study epileptogenesis mechanisms. The aim of this work was to characterize the spontaneous and synchronized rhythmic activity developed by cultured hippocampal neurons after transient incubation in zero Mg2+ to model Status Epilepticus. Cultured hippocampal neurons were transiently incubated with a Mg2+-free solution and the activity of neuronal networks was evaluated using single cell calcium imaging and whole-cell current clamp recordings. Here we report the development of synchronized and spontaneous [Ca2+]i transients in cultured hippocampal neurons immediately after transient incubation in a Mg2+-free solution. Spontaneous and synchronous [Ca2+]i oscillations were observed when the cells were then incubated in the presence of Mg2+. Functional studies also showed that transient incubation in Mg2+-free medium induces neuronal rhythmic burst activity that was prevented by antagonists of glutamate receptors. In conclusion, we report the development of epileptiform-like activity, characterized by spontaneous and synchronized discharges, in cultured hippocampal neurons transiently incubated in the absence of Mg2+. This model will allow studying synaptic alterations contributing to the hyperexcitability that underlies the development of seizures and will be useful in pharmacological studies for testing new drugs for the treatment of epilepsy.